2009
DOI: 10.1090/s0002-9947-09-04745-x
|View full text |Cite
|
Sign up to set email alerts
|

The second closed geodesic on Finsler spheres of dimension 𝑛>2

Abstract: Abstract. We show the existence of at least two geometrically distinct closed geodesics on an n-dimensional sphere with a bumpy and non-reversible Finsler metric for n > 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…In [Wan1]- [Wan3], W. Wang studied the existence and stability of closed geodesics on positively curved Finsler spheres. In [DuL1] of Duan and Long and in [Rad6] of Rademacher, they proved there exist at least two closed geodesics on any bumpy Finsler n-sphere independently. In [LoD] and [DuL2] of Duan and Long, they proved there exist at least two closed geodesics on any compact simply-connected Finsler 3 and 4 manifold.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In [Wan1]- [Wan3], W. Wang studied the existence and stability of closed geodesics on positively curved Finsler spheres. In [DuL1] of Duan and Long and in [Rad6] of Rademacher, they proved there exist at least two closed geodesics on any bumpy Finsler n-sphere independently. In [LoD] and [DuL2] of Duan and Long, they proved there exist at least two closed geodesics on any compact simply-connected Finsler 3 and 4 manifold.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…[1] that for every non-reversible Finsler metric on S 2 , there are two geometrically distinct closed geodesics. Independently, Duan and Long [2] and the author [6] showed that on an ndimensional sphere with a bumpy non-reversible Finsler metric, there are at least two geometrically distinct closed geodesic for all n > 2. A recent survey on existence results for closed geodesics on Finsler manifolds is Ref.…”
Section: Introductionmentioning
confidence: 99%
“…But when the dimension of a compact simply connected manifold is greater than 2, we are not aware of any multiplicity results on the existence of at least two closed geodesics without pinching, generic or bumpy conditions even on spheres (cf. [1][2][3][4][5][12][13][14]25,[38][39][40]), except Theorem C below proved recently in [31].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Note that Claim 2 was proved in [12,39] when d is odd or h = 1, and in [40] when d = h = 2. Next we give the proof of Claim 2 in two cases for all the values of d 2 and h 1, which yields also a new proof for the results in [12,39,40]. By Lemma 2.6, for any odd integer k 2h + 1 the Betti numbers b j in this case satisfy…”
Section: Claim 2 C Is Not Completely Non-degeneratementioning
confidence: 99%